2017
DOI: 10.1089/dna.2016.3418
|View full text |Cite
|
Sign up to set email alerts
|

Wnt5a Deficiency Regulates Inflammatory Cytokine Secretion, Polarization, and Apoptosis inMycobacterium tuberculosis-Infected Macrophages

Abstract: Tuberculosis, an infectious disease caused by Mycobacterium tuberculosis (MTB), is one of the global public health catastrophes. Wnt signaling has recently been identified to exert immunoregulatory functions in a variety of inflammatory and infectious diseases, including tuberculosis. The opposite expression of Wnt5a in human and mice during MTB infection drives us to explore the roles and biological significances of reduced Wnt5a for MTB-treated mice. In our study, the reduction of WNT5A in MTB-treated mice l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…MTB infection can not only induce host macrophage apoptosis but also induce host macrophage polarization. [ 37 ] Huang et al [ 17 ] focused on the polarization of macrophages at different stages of tuberculous granuloma formation. They concluded that the polarization of macrophages was mainly M1 in the early stage of tuberculous granuloma formation, while M2-related markers gradually increased in the late stage.…”
Section: Discussionmentioning
confidence: 99%
“…MTB infection can not only induce host macrophage apoptosis but also induce host macrophage polarization. [ 37 ] Huang et al [ 17 ] focused on the polarization of macrophages at different stages of tuberculous granuloma formation. They concluded that the polarization of macrophages was mainly M1 in the early stage of tuberculous granuloma formation, while M2-related markers gradually increased in the late stage.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to what we demonstrated for human myeloid cells in the current study, Toll/TLR-signalling induces the expression of WntD in the fly 28 . Further, in infection models of Wnt5a (mouse) or WntD ( D. melanogaster ) deficiency, an attenuated phenotype was observed in the former (because of reduced levels of pro-inflammatory cytokines) 37 , and in sharp contrast, an increased lethality was reported in the latter 28 . This was ascribed to the fact that the non-canonical WntD protein is a feedback inhibitor of Dorsal/NFκB-induced inflammation 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that macrophages are phagocytes at the frontline of the host immune defense against MTB pathogens, [1] host macrophage apoptosis, and release of inflammatory cytokines as an important defense response to resist MTB pathogens. [3,22,23] In many cell types, GJs can transmit apoptotic signals to control the destiny of cells that are associated with the expression of Cx43. [2426] Furthermore, researchers [10] have reported that Cx43 induces apoptosis of pancreatic cancer cells and apoptosis through the mitochondrial apoptotic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…[1] When MTB encounters a host, the host macrophages trigger apoptosis and release inflammatory factors to eliminate MTB pathogens, which are the important host immune defense mechanisms. [2,3] Thus, increasing reports have explored the mechanisms between MTB and host macrophage, but the cell-mediated immune responses in host macrophages are still unclear.…”
Section: Introductionmentioning
confidence: 99%